Upaya Pendayagunaan Limbah Pertanian sebagai Pakan Unggulan Musim Kemarau di Lahan Kering - Markus Miten Kleden; Mariana Nenobais (Jurnal Pemberdayaan Masyarakat, 2018)
Limitation of feed and low nutrient consumption in dry season cause a longer period of cattle fattening. The problems can be overcome by applying a cheaper and easier technology namely feed conservation technology. Method applied were extension, training, and mentoring. The result showed that the farmers’ participation were very active refers to their present and questiones raised deal with the materials presented. The highly participation also found during the training and mentoring since the feed conservation technology was an innovative activity and high benefit. The activities result were two units of representative model cattle cage due to clean and hygienic aspects, one unit of feed storage, 400 kg corn straw silage, 300 kg rice straw ammoniation, and 100 kg concentrate.